Antimicrobial food packaging: potential and pitfalls - Malhotra, Bhanu; Keshwani, Anu; Kharkwal, Harsha (Frontiers in Microbiology, 2015)
Nowadays food preservation, quality maintenance, and safety are major growing concerns of the food industry. It is evident that over time consumers’ demand for natural and safe food products with stringent regulations to prevent food-borne infectious diseases. Antimicrobial packaging which is thought to be a subset of active packaging and controlled release packaging is one such promising technology which effectively impregnates the antimicrobial into the food packaging film material and subsequently delivers it over the stipulated period of time to kill the pathogenic microorganisms affecting food products thereby increasing the shelf life to severe folds. This paper presents a picture of the recent research on antimicrobial agents that are aimed at enhancing and improving food quality and safety by reduction of pathogen growth and extension of shelf life, in a form of a comprehensive review. Examination of the available antimicrobial packaging technologies is also presented along with their significant impact on food safety. This article entails various antimicrobial agents for commercial applications, as well as the difference between the use of antimicrobials under laboratory scale and real time applications. Development of resistance amongst microorganisms is considered as a future implication of antimicrobials with an aim to come up with actual efficacies in extension of shelf life as well as reduction in bacterial growth through the upcoming and promising use of antimicrobials in food packaging for the forthcoming research down the line.